Largest Rises of Swedish Treelines, Consistent with Climate Change Since the Early-20th Century - Leif Kullman (Challenging Issues on Environment and Earth Science Vol. 6, 2021)
Treeline advance during the past 100 years was assessed by repeat in situ measurement at 14 locations distributed along the entire Swedish Scandes, c. 800 km from south to north. Concerned species were mountain birch (Betula pubescens ssp. czerepanovii), Norway spruce (Picea abies), Scots pine (Pinus sylvestris) and rowan (Sorbus aucuparia). Treeline was narrowly defined as the highest elevation with trees, at least 2 m tall. In order to elucidate the full effect and power of climate change on the treeline area, focus is on sites with the most extensive treeline shifts, according to prior regional surveys. Thereby, local constraints (topoclimate) were minimized. Betula. Picea and Sorbus accomplished treeline rise predominantly by phenotypic height growth increment of old-established krummholz, while Pinus responded by establishment and growth of new specimens. The largest upshifts, irrespective of species, were in the order of 200 m (max. 245 m). In perspective of historical treeline shifts, the new and higher treelines are close to the position prevailing about 7000 years ago. In contrast to previous generalizations, no obvious differences existed between southern and northern Scandes. Based on a common temperature lapse rate of 0.6°C per 100 m altitude and recorded regional and centennial summer warming of 1.7°C, the observed rise appears as a fully expected response. This kind of performance indicates that, at optimal sites, treelines are in equilibrium with climate at a centennial scale, in cases of climate warming.